Extracting histones for the specific purpose of label‐free MS. Issue 23 (December 2016) - Govaert, Elisabeth; Van Steendam, Katleen; Scheerlinck, Ellen; Vossaert, Liesbeth; Meert, Paulien; Stella, Martina; Willems, Sander; De Clerck, Laura; Dhaenens, Maarten; Deforce, Dieter
Abstract : Extracting histones from cells is the first step in studies that aim to characterize histones and their post‐translational modifications (hPTMs) with MS. In the last decade, label‐free quantification is more frequently being used for MS‐based histone characterization. However, many histone extraction protocols were not specifically designed for label‐free MS. While label‐free quantification has its advantages, it is also very susceptible to technical variation. Here, we adjust an established histone extraction protocol according to general label‐free MS guidelines with a specific focus on minimizing sample handling. These protocols are first evaluated using SDS‐PAGE. Hereafter, a selection of extraction protocols was used in a complete histone workflow for label‐free MS. All protocols display nearly identical relative quantification of hPTMs. We thus show that, depending on the cell type under investigation and at the cost of some additional contaminating proteins, minimizing sample handling can be done during histone isolation. This allows analyzing bigger sample batches, leads to reduced technical variation and minimizes the chance of in vitro alterations to the hPTM snapshot. Overall, these results allow researchers to determine the best protocol depending on the resources and goal of their specific study. Data are available via ProteomeXchange with identifier PXD002885.